Mathematics
Monnier975
2021-05-16 15:56:06
using A(x)=x(48-x) find the following: a.A(10) b.A(20) c.A(28) d.A(x)=0
ANSWERS
lovebug382002
2021-05-16 21:33:58

  A(x) = x(-x + 48)   A(x) = x(-x) - x(48)   A(x) = -x² - 48x A(10) = -(10)² - 48(10) A(10) = -100 - 480 A(10) = -580   A(x) = x(-x + 48)   A(x) = x(-x) - x(48)   A(x) = -x² - 48x A(20) = -(20)² - 48(20) A(20) = -400 - 960 A(20) = -1360   A(x) = x(-x + 48)   A(x) = x(-x) - x(48)   A(x) = -x² - 48x A(28) = -(28)² - 48(28) A(28) = -784 - 1344 A(28) = -2128 A(x) = x(-x + 48) A(x) = x(-x) - x(48) A(x) = -x² - 48x A(0) = -(0)² - 48(0) A(0) = 0 - 0 A(0) = 0  

ADD ANSWER